2017
DOI: 10.18069/firatsbed.346489
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Si̇ber Zorbaliğa Yöneli̇k Duyarliliklarinin Farkli Deği̇şkenler Açisindan İncelenmesi̇

Abstract: Bu araştırmanın amacı, Bilgisayar ve Öğretim Teknolojileri Eğitimi (BÖTE) bölümü öğretmen adaylarının siber zorbalık duyarlıklarını çeşitli değişkenler açısından incelemektir. Araştırma İstanbul'da öğrenim gören 352 BÖTE öğretmen adayı üzerinde yürütülmüştür. Araştırmada verilerin toplanması amacıyla araştırmacı tarafından geliştirilen kişisel bilgi formu ve Tanrıkulu, Kınay ve Arıcak (2011) tarafından geliştirilen Siber Zorbalık Duyarlılık Ölçeği kullanılmıştır. Verilerin değerlendirilmesinde tanımlayıcı ista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
2
5
1
2
Order By: Relevance
“…shows that college students who participated in this study possess high levels of cyberbullying awareness. Results of this study are similar to findings obtained from a variety of studies conducted by Gezgin and Çuhadar (2012), Uysal, Duman, Şahin, and Yazıcı (2014), Aktan and Çakmak (2015), Dikmen and Çağlar (2017), Odacı and Çelik (2018), Kozan and Özek (2019), Bridge and Doğan (2019), Hendekçi andKadiroğlu (2020), andGelmez (2020). Similarly, in their study, Uysal, Duman, Şahin, and Yazıcı (2014) found that participants were well aware of the types of cyberbullying they might encounter in digital environments and tend to take necessary measures to ensure their personal cybersecurity against potential cyberattacks.…”
Section: Analysis Of the Question "supporting
confidence: 90%
See 1 more Smart Citation
“…shows that college students who participated in this study possess high levels of cyberbullying awareness. Results of this study are similar to findings obtained from a variety of studies conducted by Gezgin and Çuhadar (2012), Uysal, Duman, Şahin, and Yazıcı (2014), Aktan and Çakmak (2015), Dikmen and Çağlar (2017), Odacı and Çelik (2018), Kozan and Özek (2019), Bridge and Doğan (2019), Hendekçi andKadiroğlu (2020), andGelmez (2020). Similarly, in their study, Uysal, Duman, Şahin, and Yazıcı (2014) found that participants were well aware of the types of cyberbullying they might encounter in digital environments and tend to take necessary measures to ensure their personal cybersecurity against potential cyberattacks.…”
Section: Analysis Of the Question "supporting
confidence: 90%
“…revealed that college students' levels of cyberbullying awareness significantly differ based on their sex, but there wasn't any statistically significant difference found between college students' sex and their ability to ensure their personal security; the difference regarding levels of cyberbullying awareness favors female students. A close scrutiny of a variety of previous studies in the relevant literature that target students from different ages (middle school, high school, college students) shows that there is a statistically significant relationship between participants' levels of cyberbullying awareness and sex; female participants were found to possess higher levels of cyberbullying awareness compared to male participants in many studies (Aktan and Çakmak 2015;Ata and Adnan, 2016;Bridge and Duman, 2019;Dikmen and Çağlar, 2017;Gelmez 2020;Gezgin, and Çuhadar, 2012;Hendekçi and Kadiroğlu, 2020:21;Horzum and Ayas, 2013;Odacı and Çelik, 2018;Peker, 2019;Pınar, Cesur, Koca, Sayın, and Sancak, 2017).…”
Section: Analysis Of the Question "mentioning
confidence: 99%
“…Yürütülen bu çalışmada öğretmen adaylarının siber zorbalıkla ilgili farkındalık düzeylerinin orta düzeyde olduğu tespit edilmiştir. İncelenen literatür ışığında öğretmen ve öğretmen adaylarının siber zorbalık farkındalık düzeylerinin yüksek (Dikmen, 2015;Dikmen & Çağlar, 2017;Gezgin & Çuhadar, 2012;Odacı & Çelik, 2018;Toprak, 2018) ve orta düzeyde (Sezer, Yılmaz & Karaoğlan, 2015) olduğu görülmektedir. Sezer, Yılmaz ve Karaoğlan (2015)'ın çalışmasının bu çalışmayla paralellik gösterdiği görülmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…Bu çalışmalar bu sonuç açısından araştırma ile paralellik göstermektedir. Bunun aksine internette daha fazla zaman harcayan kişilerin farkındalık düzeylerinin daha yüksek olduğu (Sezer, Yılmaz & Karaoğlan, 2015) ve anlamlı farklılığın oluşmadığı (Dikmen & Çağlar, 2017;Gezgin & Çuhadar, 2012;İnam & Öztürk, 2018;Toprak, 2018;Yenilmez & Seferoğlu, 2013) çalışmalara da rastlanmıştır. Bu sonuçlar ışığında, internette uzun süre zaman geçiren kişi, bu ortamda çok fazla etkileşimde bulunduğu için olumsuz durumlara maruz kalmış olabilir.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation